Phenylethanol Glycoside from Cistanche tubulosa Attenuates BSA-Induced Liver Fibrosis in Rats by Modulating the Gut Microbiota–Liver Axis - Xinxin Qi; Hongguang Sun; Jincun Liu; Meili Cong; Xinxuan Zhang; Yuxin Yan; Zhaolin Xia; Tao Liu; Jun Zhao (Pharmaceuticals)
This study aimed to investigate the effect of phenylethanol glycoside from Cistanche tubulosa (CPhGs) on the prevention of bovine serum albumin (BSA)-induced hepatic fibrosis in rats. Investigation of the mechanisms of the anti-hepatic fibrosis effect was focused on CPhGs’ influence on the “gut–liver” regulation, including the gut microbiota, intestinal barrier, systemic lipopolysaccharide (LPS) concentration, and LPS-related signaling pathway. The results show that CPhGs restored the diversity of gut microbiota, increased the relative abundance of Bacteroidetes, and decreased the relative abundance of Firmicutes and Proteobacteria in the fibrotic rats. In addition, CPhGs promoted the enrichment of probiotics such as Blautia, Oscillospira, Ruminococcus, Odoribacter, Bacteroides, and Parabacteroides in intestines of these rats. Furthermore, CPhGs reduced histopathological injury in the intestine and restored the tight junctions of the intestine by increasing the expression of ZO-1, occludin, and E-cadherin. CPhGs efficiently reduced serum LPS and liver lipopolysaccharide-binding protein (LBP) levels and inhibited the LPS-TLR4/MyD88/NF-κB pathway, which is related to protein expression in the liver. Correlation analysis confirmed that these beneficial bacteria were negatively associated with pathological damage, while LPS and harmful bacteria were positively associated with liver injury. Our fecal microbiota transplantation (FMT) experiment confirmed that gut microbiota is an important part of disease progression and that CPhGs is useful for the prevention and treatment of hepatic fibrosis. Our data demonstrate that the anti-hepatic fibrosis mechanism of CPhGs was mediated by regulation of the “gut–liver” axis. These results can stimulate consideration for its use in clinical practices.